Hemodynamic, hormonal and metabolic factors of fitness level at women - Walery Zukow; Nataliya L Horkovenko; Rostyslav F Hryvnak; Roman Y Romans'kyi; Lyubov I Holovach (Kazimierz Wielki University, 2017)
Background. It is known that the state of physical fitness of people who come to rehabilitation varies considerable range. We know also that this contingent characterized significant deviations in both sides of the gender and age norms of a number of parameters hemodynamic and autonomic regulation as well as of lipid and electrolytes exchange. Hence the assumptions listed parameters related to the state of the physical form. We set a goal by correlation analysis to detect hemodynamic and metabolic as well as hormonal factors of fitness level. Materials and methods. The object of observation were 29 women (average age 45 years with a range of 29-61 years) patients with chronic cholecystitis in remissionwho arrived at spa Truskavets' (Ukraine) for rehabilitation. Physical form evaluated on a 5-point Ǻstrand scale using veloergometry. State of central hemodynamics was investigated by echocardiography. Plasma levels of cortisol, aldosterone, estradiol, TSH and triiodothyronine determined by ELISA, of triacylglycerides, cholesterol in lipoproteins of different density, uric acid, phosphate, calcium, magnesium, sodium and potassium determined by methods reflometry and spectrophotometry. In addition, determined levels of sodium and potassium in erythrocytes as well as the activity of Na,K-, Ca- and Mg-ATPase of erythrocytemembranes.Testing was performed twice.Results.Ascertained wide variety of fitness level on a 5-point Ǻstrand scale: unsatisfactory in 15,5%, satisfactory in 64% and good in 20,5%. The method of correlation analysis revealed both positive (levels in plasma estradiol, cholesterol of alpha-lipoproteines, triiodothyronine, magnesium and level in erythrocytes sodium) and negative (blood pressure, levels in plasma cortisol, triacylglicerides, TTH, uric acidand Mg-ATPase activity) actotropic factors which together determine the level of physical fitness on 55%. Conclusion. Identified actotropic factors may be viewed as objects of targeting of fitness rehabilitation in women.